2010
DOI: 10.1186/1476-7961-8-8
|View full text |Cite
|
Sign up to set email alerts
|

Does improvement management of atopic dermatitis influence the appearance of respiratory allergic diseases? A follow-up study

Abstract: BackgroundAtopic dermatitis (AD) is often the prelude to allergic diseases. The aim of this study was 1) to evaluate if an integrated management regime could bring about a change in the evolution of the disease in comparison to the results of a previous study; 2) to determine whether the refinement of allergic investigations allowed to identify more promptly the risk factors of evolution into respiratory allergic diseases.MethodsThe study included 176 children affected by AD and previously evaluated between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 27 publications
1
52
0
1
Order By: Relevance
“…17 One study found that children with AD at age 9 to 16 months who had moderate to severe compared with mild disease as judged by Scoring Atopic Dermatitis (SCORAD) were more likely to have persistent AD 6 to 12 years later (SCORAD 25-50: 51.8% and SCORAD[50: 53.8% vs SCORAD < 25: 32.5%). 40 Finally, a study found that children with AD onset within the first 3 years of life who had less than or equal to 1 or more than 1 night compared with 0 nights per week of being kept awake by their rash had higher rates of persistent AD 5 years later (52.9% and 66.7% vs 42.0%). 28 …”
Section: Ad Persistence By Gendermentioning
confidence: 98%
See 1 more Smart Citation
“…17 One study found that children with AD at age 9 to 16 months who had moderate to severe compared with mild disease as judged by Scoring Atopic Dermatitis (SCORAD) were more likely to have persistent AD 6 to 12 years later (SCORAD 25-50: 51.8% and SCORAD[50: 53.8% vs SCORAD < 25: 32.5%). 40 Finally, a study found that children with AD onset within the first 3 years of life who had less than or equal to 1 or more than 1 night compared with 0 nights per week of being kept awake by their rash had higher rates of persistent AD 5 years later (52.9% and 66.7% vs 42.0%). 28 …”
Section: Ad Persistence By Gendermentioning
confidence: 98%
“…After review of the titles and abstracts, 9326 were excluded; an additional 634 articles were excluded after full-text review. In total, 46 studies were included in the review, of which 44 had valid frequency data that could be pooled, 7 had valid data to assess the effects of gender, 6,23,28,31,44,45,48 6 for allergen sensitization, 6,17,23,36,40,45 and 3 for baseline AD severity 17,28,40 on disease persistence. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram is presented in Fig 1. …”
Section: Literature Searchmentioning
confidence: 99%
“…Many epidemiological investigations have suggested that food allergy is a risk factor for the appearance of other allergic disease in later childhood (Kijima et al, 2013;PenardMorand et al, 2005;Ricci et al, 2010) and the progression of atopic disorders from AD in infants to allergic rhinitis and asthma in children is usually described as atopic march (Burgess et al, 2007;Carlsten et al, 2013;Leynaert et al, 2004;Ricci et al, 2006). The most important factor that precipitates allergic march is now considered an impaired epidermal barrier.…”
Section: Atopic Marchmentioning
confidence: 98%
“…better control of AD may reduce the risk of food allergy or asthma. An Italian study [20] suggested that early diagnosis and improved management of AD may lead to a reduction in the percentage of children evolving towards asthma from 29% to 15%. Integrated management of the allergic patient is therefore essential, treating each allergic manifestation well to try to reduce progression to or severity of associated allergic manifestations.…”
Section: Researchmentioning
confidence: 99%